Hypothalamic-Pituitary-Adrenal Axis Activity in SARS-CoV-2 Infected Noncritically Ill Hospitalized Patients - Banu, Hurjahan; Sultana, Nusrat; Shahed-Morshed, Md; Hasanat, M A; Saleh, Ahmed Abu; Arafat, Shohael Mahmud (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Objectives. This study determined the baseline hormonal levels of the hypothalamic-pituitary-adrenal axis and their associated factors in noncritically ill hospitalized patients with coronavirus disease 2019 (COVID-19). Methodology. This cross-sectional observational study was carried out in 91 noncritical RT-PCR-confirmed COVID-19 patients (18-65 years) recruited consecutively from the COVID unit, of two tertiary care hospitals over a period of six months. After screening for exclusion criteria relevant history and physical examinations were done, and blood was drawn between 07:00 am to 09:00 am in a fasting state to measure serum cortisol and plasma adrenocorticotropic hormone (ACTH) by chemiluminescent microparticle immunoassay. Result. Of 91 patients, 54, 26, and 11 had mild, moderate, and severe disease respectively. Median values of serum cortisol (p=0.057) and plasma ACTH (p=0.910) were statistically similar among the severity groups. Considering cortisol cut-off of 276 nmol/L (<10 μg/dL), the highest percent of adrenal insufficiency was present in severe (27.3%), followed by mild (25.9%) and least in moderate (3.8%) COVID-19 cases. Using the cortisol/ACTH ratio >15, only 6.6% had enough reserve. Conclusions. The adrenocortical response was compromised in a significant percentage of noncritically ill hospitalized patients with COVID-19, which is unrelated to infection severity, with greater percentages present in severely infected cases.